1996
DOI: 10.1289/ehp.96104620
|View full text |Cite
|
Sign up to set email alerts
|

Methylation study of a population environmentally exposed to arsenic in drinking water.

Abstract: Methylation is considered the detoxification pathway for inorganic arsenic (InAs), an established human carcinogen. Urinary speciation analysis is used to assess the distribution of metabolites [monomethylarsonate (MMA), dimethylarsinate (DMA), and unmethylated arsenic (InAs)], as indicators of methylation capacity. We conducted a large biomarker study in northern Chile of a population chronically exposed to high levels of arsenic in drinking water. We report the results of the methylation study, which focused… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

25
167
4
4

Year Published

1998
1998
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 262 publications
(200 citation statements)
references
References 37 publications
25
167
4
4
Order By: Relevance
“…It is worth mentioning, however, that MMA has the highest correlation coefficient among the metabolites. MMA excretion has been associated with an increased risk of arsenic-related diseases such as bladder and skin cancer (Hopenhayn-Rich et al, 1996;Chen et al, 2003;Steinmaus et al, 2006). This information supports the hypothesis that arsenic drinking water concentrations are, to some extent, good surrogates of arsenic exposure, even in populations exposed to relatively low levels of arsenic in drinking water (o50 mg/l).…”
Section: Discussionsupporting
confidence: 62%
“…It is worth mentioning, however, that MMA has the highest correlation coefficient among the metabolites. MMA excretion has been associated with an increased risk of arsenic-related diseases such as bladder and skin cancer (Hopenhayn-Rich et al, 1996;Chen et al, 2003;Steinmaus et al, 2006). This information supports the hypothesis that arsenic drinking water concentrations are, to some extent, good surrogates of arsenic exposure, even in populations exposed to relatively low levels of arsenic in drinking water (o50 mg/l).…”
Section: Discussionsupporting
confidence: 62%
“…For instance, increased presence of MA (III) in urine of a Mexican population chronically exposed to iAs in drinking water was associated with a greater risk of As-induced skin lesions [60]. Studies of populations chronically exposed to iAs from drinking water have shown that the relative proportion of urinary MA may increase with increasing dose of iAs exposure [86,87,170,171]. Higher urinary MA associated with increased exposure of iAs in drinking water, has been proposed to be a result of the inhibition of the second methylation step [172].…”
Section: Discussionmentioning
confidence: 99%
“…A high proportion of MA in urine may indicate lower methylation capacity. Age, smoking and gender seem to influence the relative distribution of methylated urinary arsenicals [85][86][87].…”
mentioning
confidence: 99%
“…If the MMA/DMA ratio is high, there is poor methylation at the second step. Population studies have demonstrated that generally the relative distribution is in the range of 10-30% InAs, 10-20% MMA, and 60-80% DMA in populations exposed to arsenic (2,13). There is an emerging hypothesis that methylated forms of arsenic may play a larger role in arsenic toxicity (14).…”
mentioning
confidence: 99%